CDNA-AFLP analysis of 1BL.1RS under water-deficit stress and development of wheat-rye translocation-specific markers. Issue 2 (3rd April 2017) - Jang, Ji Hee; Jung, Woo Joo; Kim, Dae Yeon; Seo, Yong Weon
ABSTRACT: Drought is a major stressor that severely hampers the production of many important crops. The short arm of rye ( Secale cereale ) chromosome 1 contains favourable stress-resistance alleles and is thus widely used in wheat ( Triticum aestivum ) breeding to generate 1BL.1RS translocation lines. In this study, 1BL.1RS-specific drought-responsive genes were identified using cDNA-amplified fragment length polymorphism (AFLP) analysis. Among the 144 transcript-derived fragments (TDF) differentially expressed in the 1BL.1RS line, we identified the function and chromosomal position of 84 TDF using public databases. Real-time PCR was performed to validate the results of cDNA-AFLP, and four TDF were significantly up-regulated. Furthermore, we developed two wheat-rye translocation-specific markers by comparing the TDF from the short arms of wheat and rye chromosome 1. One is specific to 1BL.1RS and the other is specific to 1AL.1RS and 1BL.1RS. Combinational use of both markers will be helpful to breed wheat possessing 1RS.